Indoor air quality : the latest sampling and analytical methods - Hess-Kosa, Kathleen (CRC, 2019)
"This is a practical, user-friendly guide to the identification and assessment of indoor air contaminants that contribute to buildingrelated illness in commercial buildings, institutions, and residences. The third edition covers basic concepts and details various approaches and up-to-date analytical methods, and it addresses some of the more recent, as well as less common, concerns on air pollutants. All chapters will be updated and also includes one completely new chapter on Inhalable Airborne Particles. All updates adhere to the latest National Ambient Air Quality Standards and other active standards"--